1993
DOI: 10.1029/93ja01178
|View full text |Cite
|
Sign up to set email alerts
|

Solar wind conditions in the outer heliosphere and the distance to the termination shock

Abstract: The Plasma Science experiment on the Voyager 2 spacecraft has measured to date the properties of solar wind protons from 1 to 40.4 AU. We use these observations to discuss the probable location and motion of the termination shock of the solar wind. A least squares fit of proton ram pressure to heliocentric distance R over this distance yields a ram pressure equal to (1.67 × 10−8 dynes cm−2) R−2.00 ± 0.02, where R is measured in astronomical units. Assuming that the interstellar pressure is due to a 5 µG magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 16 publications
5
63
0
1
Order By: Relevance
“…This lower speed was used so that the termination shock would be located fairly close to the Sun when reasonable (anticipated) values were used for interstellar conditions. The magnitudes of the simulated ram pressure fluctuations in Figure 2 are at the low end of the observed magnitudes in Figure 3 of Belcher et al [1993] and are similar to those of the fluctuations during solar minimum periods.…”
Section: Response To Large-scale Fluctuationssupporting
confidence: 66%
See 4 more Smart Citations
“…This lower speed was used so that the termination shock would be located fairly close to the Sun when reasonable (anticipated) values were used for interstellar conditions. The magnitudes of the simulated ram pressure fluctuations in Figure 2 are at the low end of the observed magnitudes in Figure 3 of Belcher et al [1993] and are similar to those of the fluctuations during solar minimum periods.…”
Section: Response To Large-scale Fluctuationssupporting
confidence: 66%
“…The termination shock in the equilibrium solution is located at about 80 AU; hence the fluctuations at 70 AU are only 10 AU upstream of the shock. The average value of the simulated ram pressure is less than the observed average value in Figure 3 of Belcher et al [1993] owing to the lower-than-observed solar wind speed used in the simulations. This lower speed was used so that the termination shock would be located fairly close to the Sun when reasonable (anticipated) values were used for interstellar conditions.…”
Section: Response To Large-scale Fluctuationsmentioning
confidence: 59%
See 3 more Smart Citations